Influence factor analysis and prediction model of successful application of high-volume Foley Catheter for labor induction - Jia Wang; Yu Cao; Lu Chen; Yan Tao; Huanhuan Huang; Chunju Miao (BMC, 2023)
Abstract Background This study aimed to establish a clinical-based nomogram for predicting the success rate of high-volume Foley catheterization for labor induction. Methods This retrospective study included 1149 full-term pregnant women who received high-volume Foley catheterization for labor induction from January 2019 to December 2021 in Changshu No.1 People's Hospital. Univariate and multivariate logistic regression analyses were performed, in which the labor induction success was set as dependent variables and the characteristics (including age, height, weight, BMI, gravidity, parity, gestational age, uterine height, abdominal circumference, cervical Bishop score, amniotic fluid index, cephalic presentation, neonatal weight, pregnancy complications, etc.) were set as independent variables. A nomogram scoring model was established based on these risk factors, and a calibration curve was plotted to verify the predictive accuracy of the model. Results The success rate of labor induction was 83.55% (960/1149). Univariate analysis revealed that the risk factors associated with the success rate of high-volume Foley catheterization for labor induction were height, pregnancy, birth, age, weight, BMI, uterine height, abdominal circumference, and hypertension. Multivariate logistic regression analysis showed that age (OR = 0.950; 95% CI: 0.904 ~ 0.998), height (OR = 1.062; 95% CI: 1.026 ~ 1.100), BMI (OR = 0.871; 95% CI: 0.831 ~ 0.913), and parity (OR = 8.007; 95% CI: 4.483 ~ 14.303) were independent risk factors for labor induction success by high-volume Foley catheterization. The area under the curve (AUC) of the receiver operating characteristic (ROC) curve in the prediction model was 0.752 (95% CI 0.716 ~ 0.788). A nomogram was constructed based on the final multivariate analysis with a corrected C-index of 0.748, which indicated that the model was calibrated reasonably. Conclusion Four risk factors were used to construct a nomogram to evaluate the success rate of high-volume Foley catheterization for labor induction. The nomogram provides a visual clinical tool to assist in the selection of the most appropriate mode of labor induction for pregnant women of different risk levels.